The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1080/14760584.2022.2013821
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of dried blood spots for serology of vaccine-preventable diseases: a systematic review

Abstract: Introduction: Venous serum and plasma are optimal specimens for serological testing but may be logistically infeasible. Dried blood spots (DBS) are a feasible alternative, provided results are adequately sensitive and specific. We aimed to assess the diagnostic accuracy of DBS to measure IgG and IgM antibodies for vaccine-preventable diseases and compare test validity of DBS with venous blood. Areas covered:In October 2020, we searched seven databases for peer-reviewed studies assessing the diagnostic accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…DBS is not the gold standard for measurement; thus, the laboratory results might differ from the ones using whole blood samples. However, several studies have been conducted to evaluate the correlation between those results [77][78][79][80][81][82][83][84], and systematic reviews demonstrated that DBS and whole blood sampling were associated with excellent accuracy and the pooled estimates of the sensitivity and specificity for those markers were higher than 97% [85][86][87]. The laboratory results in our study are consistent with those of other studies using whole blood samples.…”
Section: Plos Onesupporting
confidence: 90%
“…DBS is not the gold standard for measurement; thus, the laboratory results might differ from the ones using whole blood samples. However, several studies have been conducted to evaluate the correlation between those results [77][78][79][80][81][82][83][84], and systematic reviews demonstrated that DBS and whole blood sampling were associated with excellent accuracy and the pooled estimates of the sensitivity and specificity for those markers were higher than 97% [85][86][87]. The laboratory results in our study are consistent with those of other studies using whole blood samples.…”
Section: Plos Onesupporting
confidence: 90%
“…This performance appears to be independent of the subsequent assays used to measure antibody levels. Excellent correlation was observed between serum and DBS for measurement of anti- Shigella antibodies by ELISA, and DBS showed excellent precision and reproducibility using multiplex bead assays [ 18 ], but there is a need for additional validation studies [ 20 ].…”
Section: Serological Testing Using Dried Blood Spotsmentioning
confidence: 99%
“…A variety of samples can be used for antibody detection [ 24 ]. Serological antibody detection is primarily performed on serum, but antibodies can also be measured in eluted dried-blood spots (DBS) [ 28 ], in saliva or nasal swabs for mucosal or respiratory pathogens [ 29 , 30 ] and in cerebrospinal (CSF) fluid for neurotropic pathogens [ 31 ]. Saliva sampling is increasingly seen as an attractive option since it is easy and non-invasive [ 32 , 33 , 34 , 35 ], but quantifying antibody is complicated by the absence of standardized sampling methods [ 36 ] and inherent heterogeneity of saliva protein content across individuals [ 33 ].…”
Section: Serology To Assess Disease Burdenmentioning
confidence: 99%